2018
DOI: 10.1080/09291016.2018.1491263
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ sleep/wake patterns and school schedules: towards flexibility

Abstract: In the literature, two main trends may be identified in the countermeasures associated to adolescents' sleep restriction: sleep education and changes in the school starting times. However, school educational programs have been able to increase knowledge about sleep, which did not necessarily result in behavioral changes. Later school start times have been proposed as a strategy to reduce the adolescents' sleep restriction but there is no consensus about the change. Longitudinal studies in adolescent population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…Shifts in SST among schools participating in the COMPASS study allowed for a natural experiment to assess whether it was associated with youth sleep duration, physical activity level, and screen time. In line with past cross-sectional Canadian studies 26,27 and longitudinal and experimental evidence from other countries, [14][15][16][17][18][19][20][21]37,38 While previous experimental research has focused on longer delays, this study demonstrated that relatively minor changes may be beneficial for youth health. Short SST delays are likely more feasible and palatable to school stakeholders reluctant to delay SST.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Shifts in SST among schools participating in the COMPASS study allowed for a natural experiment to assess whether it was associated with youth sleep duration, physical activity level, and screen time. In line with past cross-sectional Canadian studies 26,27 and longitudinal and experimental evidence from other countries, [14][15][16][17][18][19][20][21]37,38 While previous experimental research has focused on longer delays, this study demonstrated that relatively minor changes may be beneficial for youth health. Short SST delays are likely more feasible and palatable to school stakeholders reluctant to delay SST.…”
Section: Discussionsupporting
confidence: 83%
“…Reviews and meta-analyses identify a continued need for prospective and experimental research, as the majority of past studies have used cross-sectional designs or lacked comparison groups. [14][15][16][17] A 2017 Cochrane review deemed existing evidence to be limited and of very low-quality, and hence, was unable to draw conclusions regarding the true beneficial and adverse effects of later SSTs. 15 Also, SST research has predominately been conducted in US schools, with only a few Canadian studies.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of adolescents and school hours, there are also individual and social types of interventions that could be implemented, such as sleep education and changes to school start times [73][74][75]. Moreover, the prolonged use of electronic devices with illuminated screens in the evening are associated with a reduction in nighttime sleepiness, poorer sleep quality, delayed melatonin production, increased body temperature, decreases in nocturnal melatonin production and daytime attention levels [76,77].…”
Section: Social Timesmentioning
confidence: 99%
“…Due to biological and environmental factors, is expected a gradual delay in chronotype during adolescence, reaching its peak at the end of puberty, which means a preference for going to bed later and waking up later 19 . Therefore, the school start time in many countries including Brazil, contradicts this factor and it requires adolescents to wake up in the early morning, inducing a situation of chronic sleep restriction 20 . Added to the sleep changes expected by age, the need of managing the sports demands with school and/or even with work demands may predispose adolescent athletes to an even poorer sleep condition 21 .…”
Section: Introductionmentioning
confidence: 99%